Cryptographic hashing algorithms used in modern blockchain systems - Кузнецов, О.О.; Горбенко, Ю.І.; Онопрієнко, В.В.; Стельник, І.В.; Мялковський, Д.В. (Radiotekhnika, 2019)
The analysis of hashing functions that are applied or can be used in various blockchain systems is carried out. In particular, the most common national and international standards are considered, which contain specifications of world-famous cryptographic hashing algorithms, and various projects for the construction of decentralized blockchain systems where these functions can be applied are investigated.